Contextualizing Critical Race Theory on inclusive education from a scholar-practitioner perspective : does it really matter? - Lalas, Jose W.; Strikwerda, Heidi Luv; Forlin, Chris (International perspectives on inclusive education ;, 2023)
Race does not only resonate with the dichotomy of blackness and whiteness but also on its impact on non-physical attributes, this includes factors such as indigenous status, social class, religion, language, ethnicity, class, gender, sexuality and immigration. The intersection of these factors are key considerations on inclusive education. Contextualizing Critical Race Theory on Inclusive Education from A Scholar-Practitioner Perspective highlights what race means across social, cultural, political, and historical categories of diverse identities. The scholar-practitioner approach employed here captures the theories, tenets, perspectives, and misconceptions of this based on its particular critical expansion in describing other related social identities that is consistent with the attributes of inclusive education. More importantly, it emphasizes the theoretical and practical use of critical race theory as an analytical tool in addressing the influence of race on inequities in school policy, curriculum, instruction, and educational programs and the impact of these on inclusive education. This volume features scholar-practitioners who research and engage in best practices using critical race theory as a lens to analyse and address the manifestations of race, racism, diversity, and inclusion in schooling.